Education and environmental sustainability: culture matters - Hikaru Komatsu; Iveta Silova; Jeremy Rappleye (Journal of International Cooperation in Education)
Purpose – Humans remain unsuccessful in their attempts to achieve environmental sustainability, despite decades of scientific awareness and political efforts toward that end. This paper suggests a fresh conceptualization, one that focuses on education, offers a fuller explanation for our lack of success and calls attention to alternatives. Design/methodology/approach – The authors first critically review mainstream approaches that have been used to achieve environmental sustainability, then introduce an alternative that the authors call the cultural approach. The authors finally discuss how educational research should be re-articulated based on the cultural approach. Findings – The authors identified three mainstream approaches – the technological, cognitive approach and behaviorist – all of which function to reproduce modern mainstream culture. In contrast, the cultural approach assumes modern mainstream culture as the root cause of environmental unsustainability and aims to rearticulate it. To elaborate a cultural approach, the authors recommend education scholars to (1) bring attention to the role of culture in sustainability and (2) identify education practices that are potentially useful for enacting a cultural shift, primarily developing richer synergies between qualitative and quantitative research. Originality/value – Unlike many previous studies in the field of education, the authors’ account highlights how current mainstream approaches used for current global education policymaking often merely reproduces modern mainstream culture and accelerates the environmental crisis. It thus proposes to redirect educational research for a cultural shift, one that allows human society to move beyond the comforting rhetoric of sustainability and face the survivability imperative.